InP membrane micro-ring resonator for generating heralded single photons. (21st October 2019) - Kumar, Rakesh Ranjan; Raevskaia, Marina; Pogoretskii, Vadim; Jiao, Yuqing; Tsang, Hon Ki
Abstract: In this paper, we experimentally verify the antibunching properties of multiple single photons located at distinct optical modes in a quantum frequency comb generated by cavity-enhanced spontaneous four-wave mixing in an InP membrane micro-ring resonator. The experimentally measured single photon conditional self-correlation parameter g H 2 0 = 0.08 ± 0.008, well below the classical regime (0.5) with the corresponding detector corrected Klyshko efficiency η k of 3%–4.2%.